2022
DOI: 10.3390/ijerph192215076
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Accidents and Close Calls in Junior Freeriders, Adolescent Alpine Skiers and Adult Freeriders—A Comparison

Abstract: Understanding factors associated with risk-taking behavior, accidents and close calls could enhance prevention strategies and thus contribute to preventing serious injury or death in the long term. The following study aims to assess these factors in junior freeride athletes in comparison with competitive alpine skiers of similar age and adult freeriders. A cross-sectional questionnaire design was used to assess risk-related variables and potential associated factors. Accident and close call involvement did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
0
3
1
Order By: Relevance
“…Our results highlighted the existence of two different relationships between risk judgment and risk taking: a negative relationship and no relationship (Mills et al, 2008; Reyna & Farley, 2006). Our results did not reflect the positive relationship between these variables highlighted by Reyna and Farley (2006), perhaps because the latter researchers studied adolescents, while we studied young adults and these populations may differ in their views of risk (Frühauf et al, 2020).…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Our results highlighted the existence of two different relationships between risk judgment and risk taking: a negative relationship and no relationship (Mills et al, 2008; Reyna & Farley, 2006). Our results did not reflect the positive relationship between these variables highlighted by Reyna and Farley (2006), perhaps because the latter researchers studied adolescents, while we studied young adults and these populations may differ in their views of risk (Frühauf et al, 2020).…”
Section: Discussioncontrasting
confidence: 72%
“…This might be because we studied adults and Kern et al studied adolescents. Adolescents' and adults' views of risk may differ (Frühauf et al, 2020). Our study found a negative relationship between risk judgment and risk taking.…”
Section: Risk Position 3 (Cluster 3): the Use Of An Additive Rulementioning
confidence: 47%
See 2 more Smart Citations